The Implementation of Extensive Reading to Improve Students’ Reading Skills SMA Negeri 4 Sembilan - ali, Yusfita; Zulfitri, Zulfitri (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2024)
Reading is one of the essential abilities that must be possessed by everyone because through reading, one can access a lot of information and knowledge. Additionally, reading is also considered one of the gateways to knowledge. The implementation of the extensive reading method can improve the reading ability of the 10th-grade students at SMA Negeri 4 Sembilan. According to researchers, the application of the extensive reading method is one way to enhance students' reading skills. The population in this study consists of 22 students from the 10th grade at SMA Negeri 4 Sembilan. This research employs two tests, namely the pre-test and post-test, and the results of these tests will be compared to determine whether there has been an improvement or not. The average score of the pre-test is 53.86. On the other hand, the average post-test score in cycle 1 is 63.86, and in cycle 2, it is 75. There were significant improvements after implementing the Extensive Reading Approach. This indicates that the use of the Extensive Reading Approach can enhance students' reading skills. By utilizing Extensive Reading in teaching reading, particularly reading skills, the reading ability of the 10th-grade students at SMAN 4 Sembilan can be improved. Students prefer this approach because it helps them in their reading. Hence, the Extensive Reading Approach can enhance students' reading skills.